IMPACT OF MOUTH BREATHING ON THE DEVELOPMENT OF THE DENTO-MAXILO-FACIAL COMPLEX IN CHILDREN AND ADOLESCENTS - Loredana Golovcencu; Laura Răschip; Diana Mirt; Roxana Faur; Carmen Savin; Ana Sîrghe; Alina Adumitroaie; Cezar Foia; Alexandrina Muntean; Daniela Anistoroaei; Vasilica Toma (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study This paper aims to identify the characteristics of mouth breathing as an oral vicious habit frequently encountered in paediatric dentistry clinical practice, evaluating the possible outcomes in regards to somatic and stomatognatic development, as well as interceptive treatment modalities. Materials and method A number of clinical case studies and review articles were evaluated, after searching databases for available papers using key words like "oral vicious habits", "mouth breathing", "interceptive treatment", "children and adolescents". Results Oral vicious habits are one of the most frequent disturbances seen by the paediatric dentist in the dental office, which often impair the child's quality of life. Vicious habits include thumb sucking, prolonged use of a pacifier, lip biting and sucking, onycophagia (fingernail biting), bruxism, oral self-harm, mouth breathing and tongue interposition. These habits have a great impact on occlusion and muscle development, causing repetitive and complex muscular contractions, with effects varying from individual to individual depending on the frequency, period and intensity of the habit. Conclusions Mouth breathing is an oral vicious habit which can induce numerous negative effects on the development of the stomatognatic system, therefore the identification, interception and early intervention on oral breathing should be a desiderate of every paediatric dentist's office.